Biochemical characterization of recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) protein from Leucaena leucocephala was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. Optimum pH for forward and reverse reaction was found to be 6.5 and 7.8 respectively. The enzyme was most stable around pH 6.5 at 25 degrees C for 90 min. The enzyme showed k(cat)/k(m) for feruloyl, caffeoyl, sinapoyl, coumaroyl CoA, coniferaldehyde and sinapaldehyde as 4.6, 2.4, 2.3, 1.7, 1.9 and 1.2 (x10(6) M-1 s(-1)), respectively, indicating affinity of enzyme for feruloyl CoA over other substrates and preference of reduction reaction over oxidation. Activation energy, E-a for various substrates was found to be in the range of 20-50 kJ/mol. Involvement of probable carboxylate ion, histidine, lysine or tyrosine at the active site of enzyme was predicted by pH activity profile. SAXS studies of protein showed radius 3.04 nm and volume 49.25 nm(3) with oblate ellipsoid shape. Finally, metal ion inhibition studies revealed that Ll-CCRH1 is a metal independent enzyme. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Activation energy; Cinnamoyl CoA esters; Cinnamoyl CoA reductase 1; SAXS; stability

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection

Steady state fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1) and its active site mutants - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (Journal of Fluorescence, 2014)
Fluorescence quenching and time resolved fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1), a multitryptophan protein from Leucaena leucocephala and 10 different active site mutants were carried out to investigate tryptophan environment. The enzyme showed highest affinity for feruloyl CoA (K (a) = 3.72 x 10(5) M-1) over other CoA esters and cinnamaldehydes, as determined by fluorescence spectroscopy. Quenching of the fluorescence by acrylamide for wild type and active site mutants was collisional with almost 100 % of the tryptophan fluorescence accessible under native condition and remained same after denaturation of protein with 6 M GdnHCl. In wild type Ll-CCRH1, the extent of quenching achieved with iodide (f (a) = 1.0) was significantly higher than cesium ions (f (a) = 0.33) suggesting more density of positive charge around surface of trp conformers under native conditions. Denaturation of wild type protein with 6 M GdnHCl led to significant increase in the quenching with cesium (f (a) = 0.54), whereas quenching with iodide ion was decreased (f (a) = 0.78), indicating reorientation of charge density around trp from positive to negative and heterogeneity in trp environment. The Stern-Volmer plots for wild type and mutants Ll-CCRH1 under native and denatured conditions, with cesium ion yielded biphasic quenching profiles. The extent of quenching for cesium and iodide ions under native and denatured conditions observed in active site mutants was significantly different from wild type Ll-CCRH1 under the same conditions. Thus, single substitution type mutations of active site residues showed heterogeneity in tryptophan microenvironment and differential degree of conformation of protein under native or denatured conditions.
Keywords: Active site mutants; Cinnamoyl CoA reductase; fluorescence; Ligand binding; Solute quenching